2021
DOI: 10.1016/j.aninu.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary free fatty acids complex with amylose creating another form of resistant starch: Gastrointestinal formation with fowl and swine

Abstract: Fat added to poultry and swine feeds often contains abundant free fatty acids (FFA) that can impair digestible energy (DE). Placement of the fatty acid (FA) hydrocarbon chain in the helix core reformed from amylose creates a complex of both nutrients. Resulting modifications create a new structure termed the V-helix that becomes resistant to α-amylase. Granules in grain naturally contain minimal amounts of these complexes with more being generated during food manufacturing when moisture and heat release amylos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…Generally, in HAM emulsions, the lipid-amylose complex was stronger than that of NAM emulsions, which may have delayed FFA release in the small intestinal phase (Hasenhuettl, 2008). The results are in line with the previous reported study carried out by Moran (2021), where the author reviewed the role of V-helix from amylose and fatty acid (FA) complex (V-helix-FA), which resisted the action of amylase and lipase enzymes during the GIT digestion of poultry and swine. Hence, it can be concluded that the amylose content of starch alters the microstructures and rheology of W/O emulsions.…”
Section: The Extent Of Ffa Release and Starch Hydrolysis Of Emulsionssupporting
confidence: 91%
“…Generally, in HAM emulsions, the lipid-amylose complex was stronger than that of NAM emulsions, which may have delayed FFA release in the small intestinal phase (Hasenhuettl, 2008). The results are in line with the previous reported study carried out by Moran (2021), where the author reviewed the role of V-helix from amylose and fatty acid (FA) complex (V-helix-FA), which resisted the action of amylase and lipase enzymes during the GIT digestion of poultry and swine. Hence, it can be concluded that the amylose content of starch alters the microstructures and rheology of W/O emulsions.…”
Section: The Extent Of Ffa Release and Starch Hydrolysis Of Emulsionssupporting
confidence: 91%
“…Fulfilling the digestion of dietary fat like that for protein requires several pancreatic enzymes to be present and active in the lumen. Lipase, co-lipase, and phospholipase A 2 require activation of their respective pro-enzymes by trypsin with their collective efforts being performed on the fat droplet surface ( Moran, 2021 ). These proteins are hydrophilic and need to be resistant to denaturation at the fat droplet's hydrophobic surface.…”
Section: Ca 2+ and Digestionmentioning
confidence: 99%
“…Gelatinized starch is also called "starch paste" in the literature. [253][254][255][256][257] It is known that amylose and amylopectin are structurally different from each other, which means that the amylopectin fractions remain insoluble and do not suffer significantly from the effects of shear conditions. Therefore, the dissolution of the starch granules is incomplete.…”
Section: Starch: Generalities and Gelatinizationmentioning
confidence: 99%